2006
DOI: 10.1002/hep.21182
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid exerts no beneficial effect in patients with symptomatic gallstones awaiting cholecystectomy

Abstract: Ursodeoxycholic acid (UDCA) and impaired gallbladder motility purportedly reduce biliary pain and acute cholecystitis in patients with gallstones. However, the effect of UDCA in this setting has not been studied prospectively. This issue is important, as in several countries (including the Netherlands) scheduling problems result in long waiting periods for elective cholecystectomy. We conducted a randomized, double-blind, placebo-controlled trial on effects of UDCA in 177 highly symptomatic patients with galls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 30 publications
0
42
0
4
Order By: Relevance
“…UDCA has been reported to reduce the risk of biliary colic [97][98][99][100] by decreasing gall bladder motility. However, recent studies by Vennmann et al [101] involving symptomatic patients with gallstones showed no beneficial effect of UDCA. Also, a 5% increase in the rate of complications was found among the symptomatic patients.…”
Section: Current Treatments For Cholelithiasismentioning
confidence: 96%
“…UDCA has been reported to reduce the risk of biliary colic [97][98][99][100] by decreasing gall bladder motility. However, recent studies by Vennmann et al [101] involving symptomatic patients with gallstones showed no beneficial effect of UDCA. Also, a 5% increase in the rate of complications was found among the symptomatic patients.…”
Section: Current Treatments For Cholelithiasismentioning
confidence: 96%
“…In about 20% of the cases, a secondary bacterial infection (most commonly by Escherichia coli, Klebsiella, Entercoccus faecalis) occurs [60,61]. After an episode of biliary pain the majority of patients develop repeated biliary symptoms [62]. The incidence of complications in these symptomatic patients is as high as 1-3% per year [58,63].…”
Section: Gallbladder Stonesmentioning
confidence: 99%
“…Indeed, a long-term study on UDCA treatment revealed a significant decrease in the incidence of acute cholecystitis (28). In contrast, a 3-months randomized placebo-controlled study with UDCA showed no beneficial effect on biliary pain or complications of gallstone disease (29). The finding of Guarino et al that UDCA treatment restores gallbladder muscle functions together with a decrease in biochemical markers of oxidative stress and inflammation (14) and the observation that the beneficial effects of UDCA appears to be at least in part independent of gallstone dissolution (28) supports the notion that UDCA mediates an antioxidant and anti-inflammatory effect on the gallbladder wall which, in turn, reduces lithogenicity of bile.…”
Section: Discussionmentioning
confidence: 99%